Aplikasi Metode Geolistrik Resistivitas untuk Eksplorasi Situs Purbakala di Candi Deres - Priyantari, Nurul; Arika, F (Jurnal Fisika FLUX, 2008)
Abstract: This research was carried out by using the Wenner configuration of 2D Resistivity method. The object from this research was the archeology rock that came from the Deres Temple, one of the available cultural inheritances in the Jember Regency territory. This rock the possibility was under the surface and could be detected from the resistivity value. From results of the research, was expected still had parts of the Deres Temple that was buried under the surface of the land. With the depth of the revolving object between 0,50 m. up to 7,91 m.. The data that was received from the calculation showed the bricks resistivity value were identical to the brick resistivity value that referred to the rock table of Roy E, 1984.